CONTRIBUTION OF USING GOOGLE CLASSROOM APPLICATION ON STUDENTS' LEARNING INTEREST AT SMK NEGERI 1 BATIPUH - Dirgantara, Septa Zela; Syahri, Budi; Lapisa, Remon; Primandari, Sri Rizki Putri (Journal of Mechanical Engineering Education (Jurnal Pendidikan Teknik Mesin), 2022)
Covid-19 makes learnings procesed carrie outs online learnings with the help of applications, at SMK N 1 Batipuh an online learning process is also carrie outs, namely withs helps of Google Classroom applications, this has an impacts on students interests in the learnings process. This condition that affects interest in learning occurs because theres are severals obstacle in online learnings processed such as internet connections that make students not understand in learnings. purposed of his studied was to finds outs how much of a contribution was made in the use of Googles Classroom on student interested in learnings lathe engineering subjects in class XI SMK N 1 Batipuh. The quantitative approachs use in this researched. A quantitatived approachs is use researchers to measured the contribution of the used Google Classroom in onlines learnings to interest in learning. In data analysis, this know thats the Sig valued is 0.0, which mean 0.05, it is stated that the data is correlated. The contribution of use of the googles classroom application to student interested in learnings is 0.970. So Ha is accept, whichs mean that theres is a contribution from the uses of Google Classroom in online learning to interest in learning. Its know thats the data from the correlations coefficients is 0.970 and the coefficients of determinations is 94%. The conclusion of this research is thats thered is a contribution betweens applications of the Googles Classrooms applications on student interested in learning in lathe engineering subjects for class XI SMK Negeri 1 Batipuh.Keywords: Contributions; Google Classroom; Interest in Learning; Lathe Machining Techniques; SMK N 1 Batipuh